THE EFFECT OF SCHOOL PROMOTION ON THE DECISIONS OF PROSPECTIVE NEW STUDENTS IN THE SELECTION OF SMAK ST. PETER KEWAPANTE - Natalia Wahyu Ningsih; Haji Amir Djonu; Nurdin Haji Abdul Rahman (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to find the effect of school promotion on the decision to choose. This research was conducted at SMAK St. Petrus Kewapante in the semester 2nd of the school year 2020-2021. The research population is 58 students. The technique used in this research is a saturated sampling technique whit total of 51 students. The method used in this research is descriptive quantitative. All statements are valid, reliable, normal, linear and non- heteroscedastic. Based on the results of simple linear regression calculations obtained that the decision to choose is 18.796 + 0.364 promotion. The results of hypothesis testing using t-test calculation obtained that the value of calculated-t is greater than the value of tabled-t (3,805 > 2,00). This means H0 is rejected and H1 is accepted. This result indicates that the coefficient of the determination (Adjusted R Square) of the indpendent variable on the dependent variable is Adjusted R Square 0,212 or 21,2%. Therefore, it can be concluded that there is a relationship between promotion and the decision to choose new students in SMAK St. Petrus Kewapante